Glassy worm-like micelles in solvent and shear mediated shape transitions. Issue 20 (10th May 2018) - Chakraborty, Kaushik; Vijayan, Kandaswamy; Brown, Andre E. X.; Discher, Dennis E.; Loverde, Sharon M.
Abstract : Solvent effect on the shape of worm-like glassy micelles as characterized both experimentally and with simulation. Abstract : The glassiness of polymer melts is generally considered to be suppressed by small dimensions, added solvent, and heat. Here, we suggest that glassiness persists at the nanoscale in worm-like micelles composed of amphiphilic diblock copolymers of poly(ethylene oxide)–polystyrene (PS). The glassiness of these worms is indicated by a lack of fluorescence recovery after photobleaching as well as micron-length rigid segments separated by hinges. The coarse-grained molecular dynamics studies probe the dynamics of the PS in these glassy worms. Addition of an organic solvent promotes a transition from hinged to fully flexible worms and to spheres or vesicles. Simulation demonstrates two populations of organic solvent in the core of the micelle—a solvent 'pool' in the micelle core and a second population that accumulates at the interface between the core and the corona. The stable heterogeneity of the residual solvent could explain the unusual hinged rigidity, but solvent removal during shear-extension could be more effective and yield – as observed – nearly straight worms without hinges.